FNR-Dependent RmpA and RmpA2 Regulation of Capsule Polysaccharide Biosynthesis in Klebsiella pneumoniae - Lin, Tien-Huang; Wu, Chien-Chen; Kuo, Jong-Tar; Chu, Hsu-Feng; Lee, Ding-Yu; Lin, Ching-Ting (Frontiers in Microbiology, 2019)
Fumarate nitrate reduction regulator (FNR) is a direct oxygen-responsive transcriptional regulator containing an iron-sulfur (Fe–S) cluster. During anaerobic growth, the [4Fe–4S] cluster in FNR (holo-FNR) binds specifically to DNA, whereas exposure to oxygen results in the loss of its DNA-binding activity via oxidation of the [4Fe–4S] cluster. In this study, we aimed to investigate the role of FNR in regulation of capsular polysaccharide (CPS) biosynthesis, serum resistance, and anti-phagocytosis of K. pneumoniae. We found that the CPS amount in K. pneumoniae increased in anaerobic conditions, compared to that in aerobic conditions. An fnr deletion mutant and a site-directed mutant (fnr3CA), with the three cysteines (C20, C23, and C29) replaced with alanines to mimic an FNR lacking the [4Fe-4S] cluster, showed marked increase in CPS amount under anaerobic conditions. A promoter-reporter assay and qRT-PCR confirmed that the transcription of the cps genes was repressed by holo-FNR. In addition, we found that holo-FNR could repress the transcription of rmpA and rmpA2, encoding cps transcriptional activators. Deletion of rmpA or rmpA2 in the Δfnr strain reduced CPS biosynthesis, suggesting that RmpA and RmpA2 participated in the holo-FNR–mediated repression of cps transcription, thereby regulating the CPS amount, serum resistance, and anti-phagocytosis. Taken together, our results provided evidence that RmpA and RmpA2 participated in the holo-FNR–mediated repression of CPS biosynthesis, and resistance to the host defense in response to oxygen availability.